The effect of buffers ph on electrophoretic purification of intracellular green fluorescent protein - Hazlin, Mohamed (2014)
The green fluorescent protein (GFP) is a 26.9kDa protein that first isolated from the jellyfish Aequorea victoria and composed of 238 amino acid residues. GFP exhibits bright green fluorescence when exposes to light in the blue to ultraviolet range. GFP has become a favourite marker in cell biology for visualisation of gene expression and protein translocation. GFP has also become a transcriptional probe for monitoring non product information and applied in photobleaching to investigate protein dynamics in living cells. Many purification methods have been developed to purify recombinant GFP to obtain high yield and purity. However, they need the preliminary cell disruption step to release the desired proteins which may causes high losses of GFP. Therefore, a direct purification method has been developed for purification of recombinant GFP using preparative native polyacrylamide gel electrophoresis (n-PAGE) in discontinuous buffer system. GFP was successfully purified from intact Escherichia coli cells. This direct purification process has eliminated the cell disruption step. For this research, about 5 mL of resolving gel mixture [acrylamide 12% (w/v)] was used to study the effect of buffers pH on electrophoretic purification of intracellular GFP using preparative n-PAGE gel column in continuous buffer system. For protein analyses, the biomass suspension and eluted sample was electrophoresed in n-PAGE slab gel. The gel was then captured using bio imaging method in order to determine the amount of GFP in biomass suspension and eluted sample. Besides, in order to determine the total protein, biomass in suspension and eluted sample was analysed using Lowry reagent method. The purity and yield for phosphate buffer (pH 6, 6.5 and 7) and glycine buffer (pH 9.5 and 10) cannot be determined. For the buffers pH ranging from 7.5 to 8.5, the purity and yield of GFP were increased. When the buffer pH was increased to 9, there was decrease in the purity and yield of GFP obtained. Hence, the best pH achieved was found to be pH 8.5 of Tris-HCI buffer wherein highest values of purity (47.6%) and yield (64.4%) were achieved. As a conclusion, this direct purification method was successfully purified the GFP throughout the preparative n- PAGE gel column and showed that the best pH to employ was 8.5 of Tris-HCI buffer. In addition, the Tris buffer pH ranging from 7.5 to 8.5 was found to give the high purification factor (8~11 times). These results proved that this preparative n-PAGE was absolutely an efficient unit operation to purify the proteins